Measuring a new aspect of ethnicity: The appropriate diversity index - Philipp Kolo (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2012)
Combined with the expansion of economic literature on the role of ethnicity, new indices were developed to do justice to its complexity. The current indices are generally based on pre-defined groups, disregarding the (dis)similarities between them. This is sufficient to calculate the most common indices of ethnic fractionalization and polarization. But they do not measure ethnic diversity as for any diversity index the introduction of distances between groups is essential. This paper includes the distance between groups as a crucial aspect of a country's ethnic set-up. Language, ethno-racial and religious characteristics are combined in a consistent way for a composite (dis)similarity value. The resulting distance adjusted ethno-linguistic fractionalization index (DELF) is based on an extensive amount of data, containing more than 12,000 groups defined along all three characteristics and covering a wide range of countries. By applying the equivalent approach as that of the diversity measure for single countries, the DELF offers an assessment of cultural differences between countries. As the new index measures a country's ethnic diversity, it is a good starting point to review some of the existing approaches linking ethnicity to economic outcomes.
Keywords: C43; D63; O10; Z10; 330; Composite Index; Distance; Ethno-Linguistic Fractionalization (ELF); Measurement; Kulturelle Identität; Ethnische Beziehungen; Multikulturelle Gesellschaft; Messung